2020
DOI: 10.15430/jcp.2020.25.2.79
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Lysine-specific Demethylase 1 Inhibitor, SP2509 Exerts Cytotoxic Effects against Renal Cancer Cells through Downregulation of Bcl-2 and Mcl-1

Abstract: Lysine-specific histone demethylase 1 (LSD1), also known as KDM1A, can remove the methyl group from lysine 4 and 9 at histone H3, which regulates transcriptional suppression and activation. Recently, high expression of LSD1 in tumors has been shown to be involved in cancer cell proliferation, metastasis, and poor prognosis. We found that SP2509, a potent and reversible inhibitor of LSD1, induced apoptosis in human renal carcinoma (Caki and ACHN) and glioma (U87MG) cells. Pharmacological inhibition and siRNA-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…To detect caspase-3 activity, Caki cells were treated with PTC596 for 24 h, harvested, and incubated with reaction buffer containing substrate [acetyl-Asp-Glu-Val-Asp p-nitroanilide (Ac-DEVD-pNA)] [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect caspase-3 activity, Caki cells were treated with PTC596 for 24 h, harvested, and incubated with reaction buffer containing substrate [acetyl-Asp-Glu-Val-Asp p-nitroanilide (Ac-DEVD-pNA)] [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…To detect caspase-3 activity, Caki cells were treated with PTC596 for 24 h, harvested, and incubated with reaction buffer containing substrate [acetyl-Asp-Glu-Val-Asp p-nitroanilide (Ac-DEVD-pNA)] [35] RNA was isolated using TRIzol reagent (Life Technologies, Gaithersburg, MD, USA). cDNA was obtained using M-MLV reverse transcriptase (Gibco-BRL, Gaithersburg, MD, USA).…”
Section: Asp-glu-val-aspase Activity Assaymentioning
confidence: 99%
“…The overexpression of KDM1A has been documented in a variety of cancers, and KDM1A inhibitors have, thus, entered clinical trial (23). KDM1A also plays a role in ccRCC, and this effect could be mediated by AR, indicating KDM1A activates downstream gene(s) to exert tumorigenic effect in ccRCC (24)(25)(26)(27). Here, we report that UBE2O is upregulated in the presence of KDM1A in ccRCC (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…We now summarize the information related to MCL-1 as a target and prognostic biomarker in RCC. It was reported that (i) RNAi-mediated silencing of MCL-1 sensitized the Bcl-2 inhibitor ABT-737 to induce apoptosis in RCC cell lines [ 56 ]; (ii) a cell-permeable pyrrazolopyrimidine derivative (compound C) enhances TRAIL-induced apoptosis in human Caki renal cancer cells by reactive oxygen species (ROS)-mediated c-FLIP(L) and MCL-1 downregulation [ 57 ], and (iii) similar results were also found with anisomycin [ 58 ], dicoumarol [ 59 ], curcumin [ 60 ], YM155 [ 61 ] and the histone lysine-specific demethylase 1 inhibitor, SP2509 [ 62 ] in RCC cells. It was also reported that Ras association domain family member 6 (RASSF6) as a tumor suppressor inhibits sorafenib resistance by repressing MCL-1 through the JNK-dependent pathway in RCC cells [ 63 ].…”
Section: Mcl-1mentioning
confidence: 97%